Looking for Law in China - Lubman, Stanley (Columbia Journal of Asian Law, 2006)
I have been looking for law in China for over forty years. When I started in 1963, only a handful of other Westerners had also embarked on what then seemed an exotic academic excursion. Since then, after U.S.- China relations were reestablished in 1972, many other Americans have had reason to join in the search. Now, the growing potency of China’s economic strength and international reach has made efforts to understand China more important than ever, and law has become a necessary medium for use in such efforts. This article offers insights into critical institutions and practices that mark the legal environment as it has been developing since 1979, when the People’s Republic of China (PRC) first gave foreign direct investment (FDI) a hesitant welcome. It analyzes the high degree of legal uncertainty that foreign investors and their Chinese counterparts have encountered and how they have coped with it. The uncertainty that initially marked the rules and vehicles for foreign investment when they were introduced has been reduced as they have matured, but as new rules are introduced, they, too, will generate new uncertainty. Chinese law relating to foreign investment is likely, for the foreseeable future, to continue to exhibit what I describe as rolling uncertainty.